2009
DOI: 10.1002/ppap.200900016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Multi‐Characterization of Plasma Polymerized Allylamine Films

Abstract: Plasma polymerized allylamine (ppAA) films were deposited in a radio‐frequency glow discharge plasma reactor using a continuous‐wave mode and varying the discharge power from 15 to 125 W. The deposition rate reached 26 nm · min−1 and was constant within at least half an hour of process. The chemical structure and elemental composition of the deposited films were investigated by Fourier transform infrared and X‐ray photoelectron spectroscopies, whereas surface properties were analyzed by atomic force microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 52 publications
4
58
0
Order By: Relevance
“…Popular strategies to modify the functionality of a surface include plasma polymerization, [3] layer-by-layer (LBL) deposition of polymers [4,5] (driven by electrostatic interactions, [6] charge transfer interactions [7] or hydrogen bonding [8] ) and the recently introduced deposition of "poly-dopamine" [9] (which is actually dopamine-melanin [10] ) by oxidation of dopamine with dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Popular strategies to modify the functionality of a surface include plasma polymerization, [3] layer-by-layer (LBL) deposition of polymers [4,5] (driven by electrostatic interactions, [6] charge transfer interactions [7] or hydrogen bonding [8] ) and the recently introduced deposition of "poly-dopamine" [9] (which is actually dopamine-melanin [10] ) by oxidation of dopamine with dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…They should be adjustable by the choice of adapted plasma process conditions. Different precursors and plasma excitation methods, process parameters and reactor geometries influence the plasma polymerization process and lead to a diversity of plasma-chemical reactions and thus to different film properties [58]. The low pressure plasma processes are the most widely used: microwave (2.45 GHz) [59] or capacitively coupled radio frequency (13.56 MHz) [59][60][61][62][63][64][65] activated [60], in planar parallel electrode plates geometry [63][64][65], in steel chamber [59,[63][64][65][66] or glass tubes [62,67,68] reactors, applying a continuous [61,67] or pulsed plasma discharge [59,[63][64][65]69].…”
Section: Organic Coatingsmentioning
confidence: 99%
“…A maximum N/C ratio of 0.19 was observed for a plasma power of 10 W. The highest N/C ratio is usually observed at lower powers due to greater retention of amine groups. [16] Further increasing the plasma power exhibited an overall downward trend with a minimum of 0.14 at 40 W. The decreasing N/C ratio with increasing plasma power has previously been observed [15,32,33] and is attributed to greater fragmentation at higher plasma powers. Previous studies of pAA deposited onto planar surfaces resulted in N/C ratios of 0.26-0.36, [32] higher than what was observed for quartz particles.…”
Section: Influence Of Plasma Power On Surface Chemistry and Humic Acimentioning
confidence: 74%
“…The decreases in the C-C, C-H and C5 5O, N-C5 5O peaks are attributed to the reduced signal from the adventitious carbon on the surface upon deposition of the ppAA film. Previous research has shown that increasing the plasma power decreases the atomic nitrogen concentration, [15,16] which was not observed for ppAA coated quartz particles. Such behavior was previously also not observed for plasma polymerized ethylenediamine coated quartz particles using the same system.…”
Section: Influence Of Plasma Power On Surface Chemistry and Humic Acimentioning
confidence: 79%
See 1 more Smart Citation